High sensitivity and specificity of a 5‐analyte protein and microRNA biosignature for identification of active tuberculosis. Issue 6 (22nd June 2021) - Pedersen, Jessica L; Barry, Simone E; Bokil, Nilesh J; Ellis, Magda; Yang, YuRong; Guan, Guangyu; Wang, Xiaolin; Faiz, Alen; Britton, Warwick J; Saunders, Bernadette M
Abstract: Objectives: Non‐sputum‐based tests to accurately identify active tuberculosis (TB) disease and monitor response to therapy are urgently needed. This study examined the biomarker capacity of a panel of plasma proteins alone, and in conjunction with a previously identified miRNA signature, to identify active TB disease. Methods: The expression of nine proteins (IP‐10, MCP‐1, sTNFR1, RANTES, VEGF, IL‐6, IL‐10, TNF and Eotaxin) was measured in the plasma of 100 control subjects and 100 TB patients, at diagnosis (treatment naïve) and over the course of treatment (1‐, 2‐ and 6‐month intervals). The diagnostic performance of the nine proteins alone, and with the miRNA, was assessed. Results: Six proteins were significantly up‐regulated in the plasma of TB patients at diagnosis compared to controls. Receiver operator characteristic curve analysis demonstrated that IP‐10 with an AUC = 0.874, sensitivity of 75% and specificity of 87% was the best single biomarker candidate to distinguish TB patients from controls. IP‐10 and IL‐6 levels fell significantly within one month of commencing treatment and may have potential as indicators of a positive response to therapy. The combined protein and miRNA panel gave an AUC of 1.00. A smaller panel of only five analytes (IP‐10, miR‐29a, miR‐146a, miR‐99b and miR‐221) showed an AUC = 0.995, sensitivity of 96% and specificity of 97%. Conclusions: A novel combination of miRNA and proteins significantly improves the sensitivity and specificity as a biosignature over single biomarker candidates and may be useful for the development of a non‐sputum test to aid the diagnosis of active TB disease. Abstract : The biomarker potential of plasma proteins to identify tuberculosis (TB) patients was examined. Six proteins were significantly elevated in TB patients with IP‐10 and IL‐6 declining with treatment. In conjunction with miRNA previously detected, a five analyte biosignature could identify TB patients with an AUC = 0.995, sensitivity of 96% and specificity of 97%. IP‐10 was the best single biomarker candidate, showing utility as a triage tool, to quickly and easily identify potential TB patients and monitor their response to therapy.